Sistem Kendali Dan Monitoring Penyiram Tanaman Cabai Menggunakan Metode Fuzzy Dengan Aplikasi Telegram - Priestaryansyah Ihwal Wiralaksana; Wahyu Setyo Pambudi; Ilmiatul Masfufiah (BEES: Bulletin of Electrical and Electronics Engineering, 2023)
The need for the staple food chili is quite high, while agricultural land in big cities is being converted into residential areas. Meanwhile, chili plants can grow and develop in a limited environment by controlling humidity, temperature and light intensity. This research aims to analyze a greenhouse monitoring control system for chili plants based on DHT 22 temperature sensor input and YL-69 humidity sensor. The method used is fuzzy mamdani to control humidity according to what the plants need. The system test results can maintain the soil moisture of chili plants at 60% - 80%. The DHT 22 sensor test worked quite well with a error temperature sensor of 0.00% - 1.12%. Overall, the temperature and humidity control system in the greenhouse can maintain stable humidity for chili plants at the desired set point.